Attending to adolescent experience: Tragic drama as a stimulus and a model - Lucy Elvis; Michela Dianetti (Journal of Philosophy in Schools)
This article argues that the Community of Philosophical Inquiry (CPI) can productively use tragedy as a stimulus. We do this by following Ann Margaret Sharp’s interest in Simone Weil and supplementing it with Iris Murdoch’s writing on art and literature. Weil and Murdoch provide accounts of the moral value of attention that are both timely and enriching for the practice of philosophy for and with young people. This approach hinges on (i) an understanding of the particular affordances of tragedy as attention-based literature and (ii) an attentive approach to stimulus presentation and exploration. Thus, we propose reading tragedies for neither their philosophical nor their cultural authority but rather because of the genre's unique affordances in relation to adolescents. Beginning by tracing Weil’s own educational practises (as a philosophy teacher in schools, and when instructing fellow workers), where she made extensive use of this genre, we move on to a broader exploration of the potential for attention Weil and Murdoch recognised in literature’s stimulation of imaginative exploration. With this in mind, we advocate for the pedagogical use of tragedies as a medium instructive in the limits of individual agency and the richness of reality. For to be moral, for Weil and Murdoch, means to be open to reality, and so to approach other people with attention. In our view, the moral values that inhabit tragedies are best explored through the community of philosophical inquiry, which can facilitate attention to the structure of adolescent experience; in particular, the conditions of adolescents who are in a moment of inheritance of a world beyond their control but in need of their care, experiencing a moment phenomenologically akin to Aristotle’s reversal and recognition. Therefore, tragedies, rather than speaking to us about the ancient past, can, in the CPI, meaningfully orient young people and those who work with them towards their present.